2011
DOI: 10.4103/0256-4947.83204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Accreditation on the Quality of Healthcare Services: a Systematic Review of the Literature

Abstract: BACKGROUND AND OBJECTIVE:Accreditation is usually a voluntary program in which trained external peer reviewers evaluate a healthcare organization's compliance and compare it with pre-established performance standards. The aim of this study was to evaluate the impact of accreditation programs on the quality of healthcare servicesMETHODS:We did a systematic review of the literature to evaluate the impact of accreditation programs on the quality of healthcare services. Several databases were systematically search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
183
1
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(219 citation statements)
references
References 29 publications
(30 reference statements)
5
183
1
13
Order By: Relevance
“…Some empirical studies found that accreditation improves patient safety, including mortality, morbidity, and the incidence of infection, [32,[36][37][38][39] and this needs to be applied to domestic research. However, the ability to generalize from the results of this study is limited because the history of Korea's accreditation system is short and few relevant studies exist.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical studies found that accreditation improves patient safety, including mortality, morbidity, and the incidence of infection, [32,[36][37][38][39] and this needs to be applied to domestic research. However, the ability to generalize from the results of this study is limited because the history of Korea's accreditation system is short and few relevant studies exist.…”
Section: Discussionmentioning
confidence: 99%
“…The accreditation issue was proposed in 2012 as a requirement for Health and medical education ministry of Iran on evaluation of hospitals in Iran with the aim of improving the quality of services and increasing patient safety (9). Some other studies conducted in this regard indicated that in organizations where accreditation has been established, high quality services are provided for patients, strengthening the confidence of the society on quality and safety of cares and services (10)(11)(12). Other studies showed no significant difference between validated hospitals and nonvalidated hospitals in terms of patient satisfaction (13).…”
Section: Introductionmentioning
confidence: 99%
“…This information is vital for both employee and the hospital and aids in the assurance that the hospital is staffed appropriately. [30,[38][39][40][41][42] Apart from being essential items in hospital management, proper personnel files are also essential for hospital accreditation. [43][44][45] Rwanda's Ministry of Health, which aims to strengthen health systems by ensuring provision of high quality services, adopted a hospital accreditation system in 2006 as one of the main strategies to improve quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Without proper personnel file management, appropriate and valid credentials and qualifications proving the healthcare professionals' competences would not be easily available. [33][34][35][36][37] Well managed personnel files allow hospitals to produce accurate, easily accessible and organized information about employee compensation and benefits; performance including evaluations and any disciplinary action; and work history including hiring, promotions, transfers, retirements and terminations. This information is vital for both employee and the hospital and aids in the assurance that the hospital is staffed appropriately.…”
Section: Introductionmentioning
confidence: 99%